Multimodal Imaging in an Unusual Cluster of Multiple Evanescent White Dot Syndrome. (11th May 2017) - Gal-Or, Orly; Priel, Ethan; Rosenblatt, Irit; Shulman, Shiri; Kramer, Michal
Abstract : Objective. To describe an unusual cluster of multiple evanescent white dot syndrome (MEWDS) encountered within a 3-month period. Methods. This retrospective observation study is comprised of seven patients who presented with MEWDS in a 3-month period in central Israel. Data were collected from patients' medical records on clinical, multimodal imaging, and viral serology findings. Results. Six women and one man of mean age 31.5 ± 7.2 years. Three reported a precedent viral infection. All had unilateral decreased vision. Funduscopy revealed foveal granularity. Main Imaging Findings. Hyperfluorescent spots on blue autofluorescence (BAF), hypofluorescent spots on indocyanine green angiography, dark lesions on infrared photos, and ellipsoid zone irregularities on spectral domain optical coherence tomography (SD-OCT). Resolution of the spots on BAF correlated with anatomic (SD-OCT) and visual recovery. OCT angiography performed following the convalescence stage demonstrated intact retinal and choroidal flow. Serologic findings were inconclusive. Conclusion. We report a unique cluster of MEWDS patients presented in a short period of time. SD-OCT findings of ellipsoid zone disruption in combination with other multimodal imaging modalities are outlined meticulously. Recognizing these imaging features along with high index of clinical suspicion is important for the diagnosis of MEWDS. Serologic testing might be considered in future patients.